THE EXISTENCE OF THE CHARACTER ANG SAN MEI IN PRAMOEDYA ANANTA TOER’S NOVEL JEJAK LANGKAH: A STUDY OF EXISTENTIAL FEMINISM - Wildhan Pratama; Jendriadi; Yanti Sariasih; Evi Desmariani (JURNAL KONFIKS, 2026)
This study aims to describe the character of Ang San Mei in Pramoedya Ananta Toer’s novel Jejak Langkah through the lens of Simone de Beauvoir’s existentialist feminism. Ang San Mei is a Chinese female character who experiences multiple layers of subordination as a woman, a member of an ethnic minority, and a colonial subject; however, she has not yet been specifically studied using existentialist feminist theory that takes into account the ethnicity and colonialism she experiences. The character of Ang San Mei was chosen for analysis because, although she has been depicted as fighting for her existence, studies on her remain very limited. This study employs a qualitative descriptive method with content analysis techniques. The data sources consist of the narratives, dialogues, and actions of the character Mei in the novel Jejak Langkah. The analytical framework is based on Beauvoir’s four strategies of transcendence: women can work, women can be intellectuals, women can work to achieve social transformation, and women refuse to internalize their subjugation. The results of the study indicate that Mei embodies all four forms of transcendence: asserting economic independence through her work as a teacher and cook; demonstrating intellectualism through geopolitical analysis and organizational awareness; contributing to social transformation through her involvement in Angkatan Muda and propaganda activities; refused to internalize her otherness by defining herself through her own will and idealism. This study concludes that despite experiencing layered subordination, Mei succeeded in transcending her social limitations and asserting herself as an autonomous subject through transcendence.